Return-to-Duty Rates Following Minimally Invasive Spine Surgery Performed on Active Duty Military Patients in an Ambulatory Surgery Center. Issue 9 (21st May 2018) - Granger, Elder; Prada, Stefan; Bereczki, Zoltan; Weiss, Michael; Wade, Chip; Davis, Reginald
Abstract: Background: Low back pain is a primary health care utilization driver in the US population. Health care evaluation visits for low back pain are as common as medical evaluation for the common cold. Low back pain is the most common reason for reductions in activities of daily living and work activity in the general population. Although these statistics are compelling, in the military population, there is arguably a significantly greater economic impact on the military population, as the cost to train, retain, and deploy a service member is a tremendous cost. Methods: The current study retrospectively examines surgical outcomes, return to duty, and patient-centric outcomes among 82 active duty or reserve military patients who underwent an outpatient minimally invasive spine surgery Laminotomy Foraminotomy Decompression for the treatment of lumbar spinal stenosis in an ambulatory surgery center. Findings: Overall, our results indicate that within the 82 active duty military service members, 100% of the service members return to duty within 3 mo. Additionally, there was a significant reduction in self-reported pain and disability 12 mo postoperative, whereas the average length of surgery was 62 min with an average estimated blood loss of 30.64 mL. Discussion: The current study indicates that minimally invasive procedures for the treatment of lumbar spinal stenosis in an ambulatory surgery center setting are an effective option for active duty servicemen to reduce return-to-duty rates and symptomatic back-related pain and disability.